2022
DOI: 10.1155/2022/9884155
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Research on the Expression Level of Matrin‐Type Zinc Finger Protein 4 Gene in T Cells of Thyroid Carcinoma Tissue

Abstract: In order to analyze the expression level of zinc finger matrin-type protein 4 (ZMAT4) gene in T cells of thyroid carcinoma (TC) tissue and its clinical significance to prognosis of patients based on bioinformatics and reverse transcription polymerase chain reaction (RT-PCR), 389 TC patients with ZMAT4 gene and its corresponding survival and prognosis are searched by the Cancer Genome Atlas database. The expression of ZMAT4 gene is compared between normal thyroid tissue and TC tissue by RT-PCR. The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studied have implicated the role of CHCHD6 in neurodegenerative diseases such as Alzheimer’s disease [ 36 ]. Though few studies have been conducted on the function of ZMAT4 , it has been implicated in myopia as well as thyroid cancer [ 37 , 38 ]. rs6474264, identified in intron 5 of ZMAT4 as being nominally significant by both measures, is protective of glaucoma medication non-adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studied have implicated the role of CHCHD6 in neurodegenerative diseases such as Alzheimer’s disease [ 36 ]. Though few studies have been conducted on the function of ZMAT4 , it has been implicated in myopia as well as thyroid cancer [ 37 , 38 ]. rs6474264, identified in intron 5 of ZMAT4 as being nominally significant by both measures, is protective of glaucoma medication non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…rs6474264, identified in intron 5 of ZMAT4 as being nominally significant by both measures, is protective of glaucoma medication non-adherence. Of note, rs7829127 and rs2137277, located in intron 1 of ZMAT4 , were found to be associated by both GWAS and meta-analysis with the risk of high myopia in the Han-Chinese [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%